Metadiscourse studies in written L2 English in the MENA region: A systematic review of literature - Khalid Benraiss; Abdelhamid M. Ahmed; Lameya M. Rezk (Social Sciences and Humanities Open)
This systematic review critically examines metadiscourse research in the MENA region, addressing its underrepresentation on the global stage. By analysing 19 out of 964 identified studies, the review highlights the overwhelming reliance on Hyland's frameworks, with 89.47 % of studies utilising his models, reflecting his significant influence in the region. However, the review uncovers significant methodological weaknesses, including inconsistent reporting, ambiguous research designs, and an over-reliance on a 'thin' approach to metadiscourse analysis. Additionally, the studies exhibit a narrow focus, both geographically and disciplinarily, with limited exploration of gender and cultural factors. These limitations hinder the comparability and generalizability of the findings, restricting the region's contribution to global metadiscourse research. The review calls for more diverse and rigorous methodologies, broader academic and geographical scopes, and greater integration of gender and cultural analyses to advance metadiscourse research in the MENA region and align it with global research standards. This study serves as a critical foundation for future research, offering clear recommendations to elevate the quality and impact of metadiscourse studies in this underexplored region.